Strategic outsourcing, profit sharing and equilibrium unemployment - Erkki Koskela; Jan König (Institute for the Study of Labor (IZA), 2008)
We analyze the following questions associated with outsourcing and profit sharing under imperfect labour markets. How does strategic outsourcing influence wage formation, profit sharing and employee effort when firms commit to optimal profit sharing before wage formation or decide for profit sharing after wage formation? What is the relationship between outsourcing, profit sharing, and equilibrium unemployment when profit sharing is also a part of a compensation scheme in all industries? We find that if firms will decide on profit sharing before the wage formation, higher outsourcing decreases wage whereas profit sharing has an ambiguous effect. Under flexible profit sharing wage is smaller than in the case of committed profit sharing. For equilibrium unemployment, we find that if there is also profit sharing in other industries, the effects of outsourcing and profit sharing on the unemployment rate is ambiguous both in the committed and flexible case.
urn:nbn:de:101:1-2008032625
Keywords: E23; 330; Outsourcing; profit sharing; labour market imperfection; employee effort; equilibrium unemployment; Outsourcing; Erfolgsbeteiligung; Lohnverhandlungen; Arbeitslosigkeit; Arbeitsmarkttheorie; Unvollkommener Markt; Theorie